Relatório de estágio supervisionado obrigatório: práticas de manejo de ovinos em pesquisa de avaliação de alimentos - Pedreno, Luciana dos Santos (Brasil, 2025)
Research involving the evaluation of alternative ingredients with potential for feeding farm animals is one of the lines of study with the largest number of scientific publications. In addition to the search for reducing feed costs in confinement systems, these researches also aim to find viable solutions to current problems such as greenhouse gas emissions. Before using a new ingredient in the diet, characteristics such as acceptability by the animal, nutritional value, digestibility, presence of beneficial or harmful compounds to the animal, among others, must be evaluated. In this context, the present report aimed to describe the activities developed during the realization of a research to evaluate an alternative ingredient in the diet of sheep. The internship was developed at the Center for Studies with Small Ruminants of Amazonas - CEPRAM/ ICSEZ, which is located at the Federal University of Amazonas (UFAM), Parintins campus. Practices involving the preparation of facilities and materials for the research were monitored, in addition to the practices of evaluation of food consumption, weight development, evaluation of blood parameters, digestibility test, slaughter and carcass evaluation.